B(C6F5)3: a lewis acid that brings the light to the solid state - Hansmann, Max M.; López-Andarias, Alicia; Rettenmeier, Eva; Egler-Lucas, Carolina; Rominger, Frank; Hashmi, A. Stephen K.; Romero-Nieto, Carlos (Angewandte Chemie. International edition, 2016)
The straightforward coordination of the Lewis acid B(C6F5)3 to classical, non-emitting aldehydes results in solid-state photoluminescence. Variation of the electronic properties of the carbonyl moieties lead to the modulation of the solid-state emission colors, covering the entire visible spectrum with quantum yields up to 0.64. Steady-state spectroscopy in combination with X-ray diffraction analysis and DFT calculations confirm that intermolecular interactions between the Lewis adducts are responsible for the observed luminescence. Alteration of the latter interactions induces, moreover, remarkable solid-state phenomena such as piezochromism. The versatility and simplicity of our approach facilitate the future development of solid-state emitting materials.